(untitled) (Czech Journal of International Relations, 2015)
Since the 1970’s the debate about the rising importance of transnational relations has existed in international relations. Apart from states, the related research also focuses on other actors, including epistemic communities. The article uses the concept of epistemic communities and finds whether the activity of epistemic communities determines the process of the international management of outer space in the case of the political negotiations relating to space debris in UNCOPUOS and UNOOSA. The activity of epistemic communities exists in the political negotiations relating to space debris in UNCOPUOS and UNOOSA, but it has not been reflected in the related scholarly literature. Epistemic communities from the nongovernmental organizations IAF, COSPAR and IISL contributed to setting the space debris problem on the agenda of UNCOPUOS. Also, under the influence of epistemic communities from the governmental organization IADC, UNCOPUOS adopted guidelines preventing the creation of further amounts of space debris.